PENGARUH DANA PIHAK KETIGA DAN MODAL SENDIRI TERHADAP PEMBIAYAAN MURABAHAH - M. Fauzan (FEBI IAIN Langsa, 2017)
This study discusses the influence of the third party funds and private capital towards the amount of murabahah financing at PT. BPRS Al-Yaqin. The purpose is to know the influence between the third party funds and private capital against the amount of murabahah financing at PT. BPRS Al-Yaqin. Sample in this research is financial report of PT. BPRS Al-Yaqin period 2013-2015 derived from the financial statements of PT. BPRS Al-Yaqin. Multiple linear regressions are used as an analytical technique. The results showed that the dependent variable of financing amount can be explained by independent variable that is the third party fund and private capital equal to 0.585 or 58% and the rest (42%) explained other variable outside variable used. Simultaneously, the third party fund and private capital variables have a positive influence on the distribution of financing fund based on F test where Fcount> Ftable (14.127 > 3.331) with the significant level of 0.000 <0.05.